Skeletonization algorithm FOR OBJECTS ON THREE-DIMENSIONAL RASTER IMAGES - D. A. Goncharov; A. M. Nedzved; S. V. Ablameyko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A skeleton building algorithm in case of lack of memory is presented. Built skeleton is topologically equivalent to the original object. Despite the fact that data are processed locally, this algorithm preserves a skeleton global attribute - centeredness. It is parallel and divided into independent stages, each of which can be substituted with alternatives. The method is based on pseudo-distance maps and constructed skeleton can be used to calculate topological as well as morphological characteristics of the object.